Pengaruh Computer-Assisted Instruction dan Pengetahuan Awal terhadap Hasil Belajar Teknik Pemesinan CNC - Hijrah Syahputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The study examined the effect of computer-assisted instruction and prior knowledge on SMK N 1 Bekasi students’ CNC machine learning outcomes, Eleventh grade. This study adopted a treatment by level 2 x 2 design. There are two types of Computer-Assisted Instruction design; Branching and Linear were used as treatment instruments and a CNC machines learning outcomes-Test was used as test instrument. Analysis of Variance (ANAVA) Two Way was used in analyzing data collection. The study has revealed that, there were significant differences in the learning outcomes-test mean scores of CAI-Branching and CAI-Linear, and the Tukey’s-test revealed a significant difference between CAI-Branching and CAI-Linear on high prior knowledge group. There was no significant difference in the learning outcomes-test mean scores of low prior knowledge groups taught using CAI- Branching and CAI-Linear.